Nociception monitors vs. standard practice for titration of opioid administration in general anesthesia: A meta-analysis of randomized controlled trials - Ma, Dandan; Ma, Jiahui; Chen, Huayong; Mu, Dongliang; Kong, Hao; Yu, Lingzhi (Frontiers in Medicine, 2022)
Background: Nociception monitors are being increasingly used during surgery, but their effectiveness in guiding intraoperative opioid administration is still uncertain. This meta-analysis of randomized controlled trials (RCTs) aimed to compare the effectiveness of nociception monitors versus standard practice for opioid administration titration during general anesthesia. Methods: We searched the electronic databases of PubMed, EMBASE, Cochrane Library, Clinical Trial, and Web of Science from inception up to August 1, 2021, to identify relevant articles, and extracted the relevant data. Intraoperative opioid administration, extubation time, postoperative pain score, and postoperative opioid consumption were compared between patients receiving nociception monitoring guidance and patients receiving standard management. The standardized mean difference (SMD), with 95% confidence interval (CI), was used to assess the significance of differences. The risk ratio (RR), with 95% CI, was used to assess the difference in incidence of postoperative nausea and vomiting (PONV). Heterogeneity among the included trials was evaluated by the I2 test. RevMan 5.3 software was used for statistical analysis. Results: A total of 21 RCTs (with 1875 patients) were included in the meta-analysis. Intraoperative opioid administration was significantly lower in patients receiving nociception monitor-guided analgesia than in patients receiving standard management (SMD, −0.70; 95% CI, −1.06 to −0.35; P < 0.0001). However, pain scores and postoperative opioid consumption were not significantly higher in the former group. Considerable heterogeneity was found among the studies (92%). Extubation time was significantly shorter (SMD, −0.22; 95% CI, −0.41 to −0.03; P = 0.02) and the incidence of PONV significantly lower (RR, 0.75; 95% CI, 0.59 to 0.96; P = 0.02) in patients receiving nociception monitoring guidance. Conclusions: Intraoperative nociception monitoring guidance may reduce intraoperative opioid administration and appears to be a viable strategy for intraoperative titration of opioids.